2011
DOI: 10.1097/inf.0b013e3181fefa05
|View full text |Cite
|
Sign up to set email alerts
|

Decline in Rotavirus Hospitalizations and Health Care Visits for Childhood Diarrhea Following Rotavirus Vaccination in El Salvador

Abstract: Rotavirus vaccination had a substantial public health impact on rotavirus disease and overall diarrhea events in El Salvador. Important age-related changes in diarrheal incidence emphasize the need for ongoing rotavirus surveillance after vaccine introduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
79
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(84 citation statements)
references
References 10 publications
3
79
0
2
Order By: Relevance
“…Despite lower efficacy in lowresource settings, the benefits of vaccination could be substantial in countries with a high baseline burden of severe rotavirus disease. Significant declines in all-cause gastroenteritis mortality and hospitalizations among children <5 years of age have been observed following rotavirus vaccine introduction in a few early-adopter countries with low child mortality [11][12][13][14][15]. The variation in efficacy by national gross domestic product [16] underscores the importance of monitoring the impact of rotavirus vaccination in low-income, high-mortality settings during routine programmatic use, where vaccine performance may differ from the optimal conditions of clinical trials.…”
mentioning
confidence: 99%
“…Despite lower efficacy in lowresource settings, the benefits of vaccination could be substantial in countries with a high baseline burden of severe rotavirus disease. Significant declines in all-cause gastroenteritis mortality and hospitalizations among children <5 years of age have been observed following rotavirus vaccine introduction in a few early-adopter countries with low child mortality [11][12][13][14][15]. The variation in efficacy by national gross domestic product [16] underscores the importance of monitoring the impact of rotavirus vaccination in low-income, high-mortality settings during routine programmatic use, where vaccine performance may differ from the optimal conditions of clinical trials.…”
mentioning
confidence: 99%
“…Two studies from two Latin American countries (Brazil, El Salvador) have reported a decline of 59% to 81% in laboratory-confirmed RVA hospitalizations among children younger than five years of age in post-vaccine years (Sáfadi et al 2010, Yen et al 2011a). …”
mentioning
confidence: 99%
“…Population-based time-trends of gastroenteritis burden before and after vaccine implementation -Four middle income countries in Latin America (Brazil, El Salvador, Mexico and Panama) have published reports on population-based time-trends of gastroenteritis and/or RVA disease burden reductions after RVA vaccine introduction (de Palma et al 2010, Lanzieri et al 2010, 2011, Richardson et al 2010, Sáfadi et al 2010, do Carmo et al 2011, Molto et al 2011, Quintanar-Solares et al 2011, Yen et al 2011a (Table I). In these countries, vaccine coverage among infants younger than one year of age with at least one dose of RVA vaccine ranged from 74-94% during the post-vaccine years for which data were evaluated.…”
mentioning
confidence: 99%
“…The safety, effectiveness and impact of rotavirus vaccine introduction in the decrease of severe gastroenteritis, hospitalizations, and deaths in some LA countries was discussed, including Mexico, El Salvador, Brazil and Panama [6][7][8][9]. Despite the worldwide and local beneficial evidence, some LA countries have still not introduced it universally due to economical reasons, among others.…”
mentioning
confidence: 99%